Ijtihad Umar Ibnu Al Khattab - Supratman, Supratman; Syukur, Syamzan; Harisa, Rahmawati (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2024)
This paper discusses the ijtihad of Umar Ibn Al-Khattab, the second caliph after Prophet Muhammad SAW, who is known as one of the most influential companions in Islamic history. Umar played a crucial role in strengthening and expanding Islam through his various ijtihad in the fields of law, social affairs, politics, and economics. This study highlights several significant decisions made by Umar, including the compilation of the Qur'an after the Battle of Yamama, the enforcement of congregational tarawih prayers during the month of Ramadan, and the expansion of the Masjid al-Haram and the Prophet's Mosque. Additionally, this paper illustrates Umar's efforts in the development of Islamic cities, the establishment of an efficient governance system, and the creation of Baitul Mal for state financial management. Umar is known as a firm, just, and innovative leader, whose contributions continue to be respected and studied by subsequent generations.